Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T20:20:23+01:00
A)
-3x=2x-10
-3x-2x=-10
-5x=-10 |:(-5)
x=2

b)
-(2x-2)=4
-2x+2=4
-2x=2 |:(-2)
x=-1

c)
2(x+1)=x
2x+2=x
2x-x=-2
x=-2

d)
-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

e)
(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x-17=3
-5x=20 |:(-5)
x=-4
2010-03-02T20:21:12+01:00
A) -3x = 2x - 10
-5x=-10
x=2
b)-(2x-2) = 4
-2x+2=4
-2x=2
x=-1
c)2(x+1) = x
2x+2=x
x=-2
d)-(4=x) = 2 (3-x)
-4+x=6-2x
3x=10
x=3i1/3
e)(x-7) - 2 (3x=5) = 3
x-7-6x+10=3
-5x+3=3
-5x=0
x=0
2010-03-03T01:03:44+01:00
A)
-3x = 2x - 10
-3x-2x=-10
-5x=-10 /:(-5)
x=2

b)
-(2x-2) = 4 /*(-1)
2x-2=-4
2x=-4+2
2x=-2 /:2
x=-1

c)
2(x+1) = x
2x+2=x
2x-x=-2
x=-2

d)
-(4+x) = 2 (3-x)
-4-x=6-2x
-x+2x=6+4
x=10

e)
(x-7) - 2 (3x+5) = 3
x-7-6x-10=3
-5x-17=3
-5x=3+17
-5x=20 /:(-5)
x=-4